Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan Pada Pt. Japfa Comfeed Indonesia,Tbk. Lampung Tengah - Linda, Wahyu Ama; Febriyanto, Febriyanto (Jurnal Manajemen DIVERSIFIKASI, 2021)
This study aims to determine the effect of compensation, work ability and work environment together on employee performance at PT. Japfa Comfeed Indonesia, Tbk. Central Lampung. This type of research is quantitative research. Data obtained from the results of a questionnaire given to 28 respondents, namely employees of PT. Japfa Comfeed Indonesia, Tbk. Central Lampung. The analysis technique used is Data Requirements Testing, Analysis Requirements Testing and Hypothesis Testing. The results of this study indicate that the Compensation Variable (X1) has a value of t count (4.040) greater than t table (2.013) or it can be seen from the significance value of 0.000 <a = 0.05. Therefore, H0 is rejected and H1 is accepted, so the compensation variable (X1) has a positive and significant effect on employee performance (Y). Providing satisfactory compensation will make employees excited and enthusiastic at work. This of course will give a better performance effect. Workability variable (X2) has a value of t (2.830) greater than t table (2.013) or can be seen from the significance value of 0.001 <a = 0.05. Therefore, Ho is rejected and H2 is accepted, so that Job Ability has a positive and significant effect on employee performance. When employees are responsive in doing the work they are assigned to, it will have an impact on the resulting performance in accordance with company standards. Work Environment variable (X3) has a value of t (2.218) greater than t table (2.013) or it can be seen from the significance value of 0.028 <a = 0.05. Therefore, Ho is rejected and H3 is accepted, so the Work Environment (X3) has a positive and significant effect on employee performance (Y). The better and conducive the employee's work environment is, the greater the work comfort you will get. Keywords: compensation, work ability and work environment, employee performance